Comparison of routing protocol performance on multimedia services on software defined network - Vivi Monita; Indrarini Dyah Irawati; Rohmat Tulloh (Institute of Advanced Engineering and Science, 2020)
Software defined network (SDN) is a new paradigm in network engineering, where control plane and data plane are separated. Data plane is carried out on each node, while a control plane is centrally located. In conventional networks, the planes are implemented in the firmware of the router. In this paper, we implemented multimedia services on SDN using exterior and interior routing protocols, such as open shortest path first (OSPF), border gateway protocol (BGP) and routing information protocol (RIP), measured the quality of service (QoS), and analyze the measurement results. The test results showed that the greater the background traffic provided, the smaller the throughput. Traffic on the network will be congested, so the available bandwidth is also increasingly used up so that the number of bits sent every second decrease. Mean opinion score (MOS) test results are 4 showing good categories based on ITU-T standards.